2004
DOI: 10.1007/s10517-005-0140-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pathomorphological study of contractile myocardium under conditions of increased left and right ventricular afterload

Abstract: Structural changes in the myocardium under conditions of increased left and right ventricular afterload were studied using polarization microscopy and histological, histochemical, and stereological methods. Increased afterload not complicated by heart failure was characterized by low number of damaged cardiomyocytes (3.3-6.5%) and moderate structural changes in the ventricular myocardium (contractures of different severity). Increased afterload complicated by heart failure was characterized by high ratio of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Moreover, in-vitro studies have shown similar intrinsic properties of myofibers from the left and right ventricles, including their response to pressure and volume overload conditions [23,24]. Because the pathophysiology of left ventricular (LV) response to chronic aortic regurgitation has been studied in great detail [25-27], it is worth considering the sequence of events here.…”
Section: Pathophysiology Of Repaired Tofmentioning
confidence: 99%
“…Moreover, in-vitro studies have shown similar intrinsic properties of myofibers from the left and right ventricles, including their response to pressure and volume overload conditions [23,24]. Because the pathophysiology of left ventricular (LV) response to chronic aortic regurgitation has been studied in great detail [25-27], it is worth considering the sequence of events here.…”
Section: Pathophysiology Of Repaired Tofmentioning
confidence: 99%
“…In addition, aggravated stenosis of the aorta was associated with reduction of NAD-diaphorase activity and increase of NADP-diaphorase activity, as a result of which their proportion decreased in comparison with the control and reached 1. cardial hyperfunction [5] or reaction to deep injuries in its structure [7]. The reactive variant was confi rmed by the results of a previous study [10] which found the most signifi cant (by volume and severity) cardiomyocyte injuries in stenosis of the aorta aggravated by heart failure. Desymapthization of the myocardium and predominance of the adrenal component in the structure of the sympathoadrenal effects on the heart could promote the development of structural and metabolic changes in contractile cardiomyocytes under conditions of complicated stenosis of the aorta [9].…”
Section: Resultsmentioning
confidence: 89%
“…Our previous studies have shown that pressure overload of one ventricle leads to an increase in the number of damaged contraction cardiomyocytes (in contrast to conduction ones) in the walls of both cardiac ventricles [7]. This means that structural disorders in contraction cardiomyocytes can be caused by changes in the heart work and by systemic alterative factors, among which the sympathoadrenal system is assumed to play an important one.…”
Section: Resultsmentioning
confidence: 99%